2017
DOI: 10.1002/14651858.cd011539.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme replacement therapy for infantile-onset Pompe disease

Abstract: The search found no trials comparing the effectiveness and safety of enzyme replacement therapy to another intervention, no intervention or placebo. One small randomized controlled trial provided no robust evidence for which dosing schedule of alglucosidase alfa was more effective to treat infantile-onset Pompe disease. It is not deemed ethical to proceed with new placebo-controlled trials, therefore a randomized controlled trial with a large sample size comparing different dosing schedules of enzyme replaceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 36 publications
1
39
0
7
Order By: Relevance
“…The algluosidase alfa dosage initially recommended was 20 mg/kg every other week for all patients with Pompe disease. Since this advice is only based on one study comparing two small groups of IOPD patients, it has been concluded that there is no robust evidence which dosing schedule is most effective in IOPD [8]. Due to the suboptimal efficacy of ERT in this age group, a substantial number of IOPD patients are now treated with higher doses than indicated in the package insert [3,6,9,15,33,47].…”
Section: Enzyme Replacement Therapy (Ert)mentioning
confidence: 99%
“…The algluosidase alfa dosage initially recommended was 20 mg/kg every other week for all patients with Pompe disease. Since this advice is only based on one study comparing two small groups of IOPD patients, it has been concluded that there is no robust evidence which dosing schedule is most effective in IOPD [8]. Due to the suboptimal efficacy of ERT in this age group, a substantial number of IOPD patients are now treated with higher doses than indicated in the package insert [3,6,9,15,33,47].…”
Section: Enzyme Replacement Therapy (Ert)mentioning
confidence: 99%
“…İnfantil tip Pompe hastalığında prenatal tanı mümkündür. Gelecekteki hedef tedavi gen tedavisidir [55,56]. Mukopolisakkoridozlar tip 1, 2, 6'da ERT ve hematopoetik kök hücre tedavisi kullanılmaktadır.…”
Section: Tedavi Ve Izlemunclassified
“…Historically, patients with infantile Pompe disease had a poor prognosis with early death secondary to cardiorespiratory failure before 1 year of age [9]. However, since 2006, the introduction of enzyme-replacement therapy has extended survival [10]. The mean age of presentation for late onset disease is 28 years, although almost one fifth present under the age of 12 years.…”
Section: Disorders Of Glycogen Metabolismmentioning
confidence: 99%